Sistem Informasi “Maintenance AC” Berbasis Web Pada PT. Unggul Bayu Pratama Jakarta - Sandra Dewi Saraswati; Yamin Nur Yamin (STMIK Budi Darma, 2019)
In the current era of globalization, advanced information technology with a computer fast. The equipment created to facilitate the work of man, while achieving good progress in the manufacture of hardware and software. Developments in the business world can not be separated from the name of the progress of information technology. The business world is now very dependent with rapid information technology development, not least in the world of business maintenance / maintenance and repair of air conditioning units. Company Profile information site about the business world that offers air conditioning maintenance services is promoting the latest information regarding maintenance and repair services of air conditioning unit to the general public. Where the content of the specialist field of business you run, if the information contact person in need of services offered, tips on caring for air conditioning units in homes and offices as well as more information about the company that is very experienced in the field of maintenance and repair of air conditioning units. So that the information obtained would be useful for the general public. Therefore, the computerized system of the previous, the manual, it is expected that the business will operate effectively and efficiently so that the system will be more than the previous sales.